Magnetic Functional Materials: Synthesis, Characterization and Application - Wang, Haiou; Yang, Dexin (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Magnetic functional materials are widely used in energy, information, and materials science and technology. There are many kinds of magnetic functional materials, and their progress is rapid. Magnetic functional materials have attracted a great deal of attention regarding their applications. Magnetic behaviors are widespread in a variety of materials, such as metals, ceramics, organics, and emerging 2D materials. The applications of magnetic materials include memories, sensors, magnetic refrigeration, drug delivery, electrochemistry, environmental protection, energy storage, and more. This Special Issue, "Magnetic Functional Materials: Synthesis, Characterization and Application", addresses existing knowledge gaps and aids advance deployment of magnetic functional materials. It consists of nine peer-reviewed papers and one editorial that cover a range of subjects and applications related to magnetic functional materials.